Pregnancy Behavior Induce Changes in Glia Cells Rattus norvegicus Offspring Brain Through Prenatal Stimulation of Holy Quran - Ridzky Berliana Kusuma; Hermanto Tri Joewono; Asfarina Zanudin (Wolters Kluwer - Medknow Publications, 2023)
Introduction: The environment influences the development of nerves in the brain from early pregnancy until newborn. The purpose of this study was to determine the response of glial cells in the fetus to the sound stimulus of the murottal Al-Qur'an in newborn Rattus norvegicus. Besides that, the goal of this study was to show that murottal Al-Qur'an has seductive chants, makraj, and tajwid, which can emit brain waves and increase the number of glial cells by decreasing stress hormones and relaxing, thereby continuing to support fetal growth and development through the increasing number of glial cells. Methods: Female Wistar were divided into two equal groups. The control group without treatment and the surah Ar-Rahman group were given exposure treatment on days 10-20 of pregnancy. At the end of the experiment, R. norvegicus was sacrificed, and the cerebrum was taken, the head weight was measured, and the left and right hemispheres were analyzed for the number of left and right glial cells. Then, the brain was prepared using hematoxylin-eosin and observed in 400 magnifying microscopes in five fields. Results: The results showed that exposure to surah Ar-Rahman murottal could increase the number of glial cells with a significant difference (P < 0.05). Conclusions: This research establishes a relationship between stimulation since pregnancy with murottal Al-Qur'an and a number of glial cells (astrocyte, oligodendrocyte, and microglia). This finding can help identify stimulation of the murottal Al-Qur'an sound during pregnancy with glial cells.